Patriot : a memoir - Navalʹnyĭ, Alekseĭ (Alfred A. Knopf, 2024)
A political freedom fighter who paid the ultimate price for his convictions recounts his political career, the many attempts on his life and the lives of the people closest to him and the relentless campaign he and his team waged against an increasingly dictatorial regime.